Are traits drivers or consequences of competition? Comments to Carmona et al - Botta‐Dukát, Zoltán (The Journal of ecology, 2021)
Carmona et al. (2019) have recently published the results of a well‐designed experiment examining the effect of functional traits on the outcome of competition. Their main conclusions were that (a) trait hierarchies better predict the strength of competition than trait differences, and (b) the consideration of intraspecific trait variation improves our ability to predict the strength of competition. They applied multi‐model inference by averaging regression coefficients. This approach is strongly criticized because it averages regression coefficients for which the meaning is conditional on the other predictors included in the model. In this paper, their data were re‐analysed using alternative methods. The results only partly support the original conclusions in that trait hierarchy proved to be obviously important in height, but not in the other three traits. Synthesis. Intraspecific trait variation contributes to a better understanding of the relationship between traits and competitive interactions. On the other hand, traits measured in focal individuals may be both drivers and consequences of competition, which makes the interpretation of the relationship more difficult. Intraspecific trait variation contributes to a better understanding of the relationship between traits and competitive interactions. On the other hand, traits measured in focal individuals may be both drivers and consequences of competition, which makes the interpretation of the relationship more difficult.